Challenges to Monetary Policy in the Czech Republic-An Integrated Monetary and Fiscal Analysis - Munoz, Sonia (IMF Working Papers; Working Paper ;, 2008)
This paper uses the Global Integrated Monetary and Fiscal Model (GIMF), a New Keynesian open-economy general equilibrium model suitable for an integrated evaluation of monetary and fiscal policies, to analyze monetary policy challenges facing the Czech Republic. In the context of the recent rising inflation pressures, we analyze how the authorities' fiscal reform package and the planned reduction in the inflation target in 2010 would weigh on the conduct of monetary policy.